Effects of Deeper Molecular Responses on Outcomes in Chronic Myeloid Leukemia Patients in Chronic Phase Treated With Imatinib Mesylate - ATAGÜNDÜZ, IŞIK; TOPTAŞ, TAYFUR (CIG MEDIA GROUP, LP, 2017)
The significance of molecular response depth is not well defined in patients with chronic phase chronic myeloid leukemia (CP-CML) under imatinib treatment. We retrospectively evaluated clinical records of 178 patients with CP-CML. Eighty-eight patients achieved complete molecular response during long term follow-up. Our results implicate that deeper molecular response is associated with improvement in disease outcome and a slight prolongation in progression-free survival. Background: The prognostic significance of complete cytogenetic response (CCyR) is well defined in patients with chronic phase chronic myeloid leukemia treated with imatinib as first-line therapy. However, the effect on outcomes of obtaining molecular response itself and the depth of it is not clear. In this study we aimed to determine the frequency of complete molecular response (CMR) during long-term follow-up and the clinical significance of CMR on patient outcomes and survival. Patients and Methods: We retrospectively evaluated the files of 178 chronic phase chronic myeloid leukemia patients using imatinib therapy. Forty-seven patients with missing data were excluded from the study and the assessment was done in 131 patients. CiviR was defined as undetectable BCR-ABL transcripts using real-time quantitative polymerase chain reaction with a sensitivity level of >= 10(4) in 2 consecutive analyses at least 3 months apart. Cytogenetic and molecular monitoring during treatment was performed according to the European LeukemiaNet recommendations criteria. Our primary objective was to analyze the association of deeper molecular response with differences in progression-free survival (PFS). Results: Eighty-eight patients (67%) achieved CMR at any time in a median of 65 months of follow-up. The rate of CMR was higher in patients who achieved CCyR at 12 months and major molecular response (MMR) at 18 months. Fewer events occurred in the CMR group than the MMR group (26.1% vs. 50.0%). Overall survival was not different in both groups. CMR was associated with longer PFS with borderline significance. Conclusion: Prolonged imatinib therapy helps to achieve a deeper molecular response in the long-term. Achieving deeper molecular response at any time positively affects maintaining the cytogenetic and molecular responses, and decreases the transformation to accelerated and/or blastic phase. The slight prolongation in PFS did not reach statistical significance.
Keywords: BCR-ABL; Disease outcome; Molecular monitorization; Progression-free survival; Tyrosine kinase inhibitors; DIAGNOSED CHRONIC-PHASE; CHRONIC MYELOGENOUS LEUKEMIA; ALPHA PLUS CYTARABINE; FOLLOW-UP; 800 MG; INTERFERON; NILOTINIB; PREDICTS; TIME; DASATINIB